Regional water right distribution model of multi-objective programming - An empirical study based on the data in Ningxia - Tian Gui-liang; Xu Chang-xin; Xie Wen-xuan; Pan Rong (2010 International Conference on Management Science & Engineering 17th Annual Conference Proceedings, 2010)
Under the background of frequent occurrence of extreme drought as well as increasing attention to water shortage, regional water right distribution has become a vital approach for local government to advocate water right and manage water resource. The connotation along with subject and object of regional water right are investigated in this article. The manifestations of regional water right include life water right, ecological water right and productive water right. Multi-objective programming model of regional water right distribution in the fields of life, ecology and production is established taking social, ecological and economic targets into account. In accordance with the principle that basic water right superiors than public water right and competitive water right, the distribution priority is confirmed by questionnaires design and AHP method. Finally, empirical research is conducted by data from Ningxia and results are obtained under the condition of objects equilibrium. 0.3188 billion m 3 water should be distributed to life activities and 0.1109 billion m 3 water should be distributed to ecological activities, 7.3331 billion m 3 to production activities according to the abovementioned empirical research.